1997
DOI: 10.1002/(sici)1096-8652(199706)55:2<104::aid-ajh9>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of α-thalassemia on sickle-cell anemia linked to the Arab-Indian haplotype in India

Abstract: Two population groups from Western India with a high prevalence of the S gene, one tribal (Valsad) and the other nontribal (Nagpur), were studied. The S gene frequency in both populations was similar (0.22 vs. 0.23), but not the clinical expression of sickle-cell anemia (SS): the sickle homozygotes in the tribal group appeared to have a mild clinical course, whereas the majority in the nontribal group exhibited a more severe clinical phenotype. Both tribal and nontribal SS patients had a similarly high mean he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
52
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 18 publications
6
52
1
Order By: Relevance
“…Moreover, this study also shows the presence of both Hb S and b-thal in the studied population. Furthermore, a + -thal is a well-known genetic factor that modulates the disease severity in sickle cell anemia and b-thal (21)(22)(23)(24)(25)(26). High prevalence of G6PD deficiency in the study area lends further support to our findings.…”
supporting
confidence: 81%
“…Moreover, this study also shows the presence of both Hb S and b-thal in the studied population. Furthermore, a + -thal is a well-known genetic factor that modulates the disease severity in sickle cell anemia and b-thal (21)(22)(23)(24)(25)(26). High prevalence of G6PD deficiency in the study area lends further support to our findings.…”
supporting
confidence: 81%
“…Sickle-cell anemia individuals with -α 2 3.7 kb thal and a CAR/Ben genotype seem to have a smaller number of painful episodes. Mukherjee et al (1997) reported a low incidence of painful crisis in individuals with -α 2 3.7 kb thalassemia and the CAR/CAR genotype, conflicting with an earlier report of Billett et al (1995) which suggest that the presence of a-thalassemia and others epistatic effects, most likely involving vascular response, should be influence the capacity of the sickle cells to adhere to the vascular endothelium. In our study, HbF levels did not show a significant difference among α-thalassemia genotypes (i.e., those with and without the α 2 3.7 kb deletion), this observation being consistent with previous reports (Figueiredo et al, 1996).…”
Section: Discussionmentioning
confidence: 79%
“…The genotype of α-thalassemia that is prevalent in India is α+, which is clinically silent both in the heterozygous and homozygous states. Hence, it is free from morbidity [3]. …”
Section: Introductionmentioning
confidence: 99%